PENGARUH MOTIVASI,MINAT BELAJAR DAN LINGKUNGAN TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA - Laili Habibah Pasaribu (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
The purpose and formulation of the problem of this study is to determine whether there is an influence of motivation, interest in learning, and the environment on students' mathematics learning achievement. This research method is quantitative descriptive research. The sample in this study was 87 students drawn from the total population of data and can represent the entire population with the Slovin formula. The results of this study were tested with multiple correlation tests resulting inF a value calculated of 87.469 at sig level 0.000, which means significant. From the list of F distributions with the numerator dk 1 and the denominator dk (n-4) = 83 at the real level α = 0.05 obtained F table = 4.04. then concluded that there is a significant influence with the provisions of the F value calculated > Ftable = 87.469> 4.04. By being obtained like that, the researcher concludes that a student's achievement is very influential on his interest in learning, his motivation to learn must also be enthusiastic. Apart from these two factors student achievement is also a very big influence on the environment in which a student is located